Toolkit for cellular studies of mammalian mitochondrial inorganic polyphosphate - Hambardikar, Vedangi; Akosah, Yaw A.; Scoma, Ernest R.; Guitart-Mampel, Mariona; Urquiza, Pedro; Da Costa, Renata T.; Perez, Matheus M.; Riggs, Lindsey M.; Patel, Rajesh; Solesio, Maria E. (Frontiers in Cell and Developmental Biology, 2023)
Inorganic polyphosphate (polyP) is an ancient polymer which is extremely well-conserved throughout evolution, and found in every studied organism. PolyP is composed of orthophosphates linked together by high-energy bonds, similar to those found in ATP. The metabolism and the functions of polyP in prokaryotes and simple eukaryotes are well understood. However, little is known about its physiological roles in mammalian cells, mostly due to its unknown metabolism and lack of systematic methods and effective models for the study of polyP in these organisms. Here, we present a comprehensive set of genetic modified cellular models to study mammalian polyP. Specifically, we focus our studies on mitochondrial polyP, as previous studies have shown that potent regulatory role of mammalian polyP in the organelle, including bioenergetics, via mechanisms that are not yet fully understood. Using SH-SY5Y cells, our results show that the enzymatic depletion of mitochondrial polyP affects the expression of genes involved in the maintenance of mitochondrial physiology, as well as the structure of the organelle. Furthermore, this depletion has deleterious effects on mitochondrial respiration, an effect that is dependent on the length of polyP. Our results also show that the depletion of mammalian polyP in other subcellular locations induces significant changes in gene expression and bioenergetics; as well as that SH-SY5Y cells are not viable when the amount and/or the length of polyP are increased in mitochondria. Our findings expand on the crucial role of polyP in mammalian mitochondrial physiology and place our cell lines as a valid model to increase our knowledge of mammalian polyP and mitochondrial physiology.